2013
DOI: 10.1111/1753-6405.12113
|View full text |Cite
|
Sign up to set email alerts
|

Low seroprevalence of Murray Valley Encephalitis and Kunjin viruses in an opportunistic serosurvey, Victoria 2011

Abstract: Objective: To assess evidence of recent and past exposure to Murray Valley encephalitis virus (MVEV) and West Nile clade Kunjin virus (KUNV) in residents of the Murray Valley, Victoria, during a period of demonstrated activity of both viruses in early 2011. Methods: A cross‐sectional serosurvey using two convenience samples: stored serum specimens from a diagnostic laboratory in Mildura and blood donors from the Murray Valley region. Specimens were collected between April and July 2011. The main outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…This was consistent with previous experience in these areas. A serosurvey conducted in Victoria following the 2011 outbreak found very low levels of MVEV antibody, especially in people born since the last epidemic there in 1974 [46]. This is a similar outcome to a serosurvey of people living in high-risk areas of Victoria and NSW conducted in 1991 [47].…”
Section: Discussionsupporting
confidence: 56%
“…This was consistent with previous experience in these areas. A serosurvey conducted in Victoria following the 2011 outbreak found very low levels of MVEV antibody, especially in people born since the last epidemic there in 1974 [46]. This is a similar outcome to a serosurvey of people living in high-risk areas of Victoria and NSW conducted in 1991 [47].…”
Section: Discussionsupporting
confidence: 56%
“…Paradoxically, there were very few human clinical cases attributed to infection with WNV KUN from epidemic foci during 2011 [6]. Furthermore, a cross-sectional serosurvey of 1,115 human serum specimens from a focus of WNV KUN in Victoria found less than 0.3% were IgM positive, providing little evidence of recent exposure amongst the human population [8]. In contrast to North American WNV, which is highly pathogenic in a number of bird species [9,10], there was no increased mortality observed in birds during the 2011 outbreak [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, these seroprevalences are considerably lower than seen in previous serosurveys conducted in the Murray Valley region of NSW between 1991 and 2011, where WNV KUN seroprevalences had been observed to range between 2.2 and 2.5% in the human population (21, 22). Higher WNV KUN seroprevalence rates, ranging from 2.1 to 3.1%, have also been observed in Victorian residents (21, 23). It is possible that our results are biased because of the small sample size relative to previous studies and the fact that we studied a seemingly health conscious subset of the population, i.e., blood donors, who may take measures to limit their exposure to mosquitoes and thus arbovirus disease in accordance with Public Health recommendations.…”
Section: Discussionmentioning
confidence: 86%
“…Rather, MVEV tends to occur in the Murray Valley basin and occurrence is governed by rainfall and the resulting migration of birds. Previous VIC-based studies observed a MVEV seroprevalence of 3.7% ( n  = 2,783) in 1991–1992 and 2.2% ( n  = 1115) in 2011 (21, 23). …”
Section: Discussionmentioning
confidence: 87%